Pendidikan dan Pandemik Covid-19 (Pengalaman dari Arab Saudi dalam Perspektif Soft Sytem Methodology (SSM)) - Trisnawati, Trisnawati; Fitriati, Rachma (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
Information communication technology (ICT) continues to increase human activities. Higher Education Institutions around the world have used this technology to enhance learning experiences and overcome geographic barriers in the creation and delivery of educational knowledge. In this context, online distance education (PJJ) has become popular in Higher Education as an educational process that can help them achieve international prestige as well as increase their student numbers through ICT-based learning. Including in the current Covid-19 pandemic era, the PJJ method is the only solution in this pandemic. However, the successful implementation of PJJ using ICT presents a number of challenges. This paper explores institutional, technological, cultural and learner challenges, the manifestation of which can vary from country to country using Checkland's Soft System Methodology (SSM) as a learning methodology. We present an empirical examination of the challenges of PJJ in the context of Saudi culture during the COVID-19 pandemic.